Study of the lytic polysaccharide monooxygenases MtLPMO9A for biotechnological applications - Sepulchro, Ana Gabriela Veiga (2021)
The growing demand for energy and the need to replace chemical technologies and non- renewable fuels in a sustainable and efficient way place the bioconversion of lignocellulosic biomass at the center of the current energy discussion. However, the high recalcitrance of this material makes its degradation a non-trivial task, even after undergoing physical-chemical pretreatments. The biotechnological solution applied to overcome this problem is the use of enzymes capable of acting synergistically in the efficient degradation of this biopolymers. In this context, lytic polysaccharide monooxygenases (LPMOs) oxygen and copper-dependent enzymes that demonstrate the ability to improve the performance of traditional hydrolytic enzymes have emerged. As it is an enzyme class with many peculiarities in relation to the others traditionally used in biomass bioconversion, the knowledge acquired in the last decade is disconnected, approaching several aspects of the enzyme in isolation. The present work aims to study the LPMO from Thermothelomyces thermophilus M77 (formerly Myceliophthora thermophila), connecting the main study points applied in LPMOs in a single enzyme. In the first part, a sequence and active site analysis was performed, as well as a biochemical characterization. The enzyme has a well-preserved active site among the LPMOs of the AA9 family, and has only the LPMO domain in its sequence. The enzyme has high thermal stability over a wide pH range (4 to 10), has a better performance on an amorphous cellulosic substrate and has ascorbic acid, as the preferred reducing agent among those tested. Regarding the co-substrate origin, MtLPMO9A was able to use both H2O2 and O2, however, for both cases, the need for high levels of reducing agent was observed. Another analysis revealed that the enzyme has a synergistic effect on cellulosic pulp degradation when combined with traditional cellulases cellobiohydrolase (Cel7A) and endoglucanase (Cel7B); leading to an increase of 83.17% and 84.00% in products generated in association with Cel7A and Cel7B respectively. The second part of the work was concerned with evaluating the use of MtLPMO9A in photoactivated systems in the presence of photosensitizers. Starting with the commonly used chlorophyllin, this system made the enzyme much more efficient in the first reaction times, increasing the enzymatic activity in relation to the standard system. The investigation of the use of methylene blue as a photo-activator of MtLPMO9A was also carried out, determining the ideal conditions of this system. Thus, it was possible to generalize the LPMO/photosensitizer interaction, stating that the good performance of the latter in activating the enzyme is related to the mechanism by which it returns to its grounded state (Type I). The results obtained lead to an understanding of the mechanism of action of MtLPMO9A, as well as pointing to its great potential in adding enzyme mixtures, increasing the efficiency of biomass conversion. In addition, by connecting the various aspects studied in LPMOs, such results help to build a solid and connected knowledge of this class of enzymes.